Agrarian Legal Education and Land Dispute Settlement Strategies for the Residents of Seri Dalam Village, Tanjung Raja Subdistrict, Ogan Ilir Regency - Ledy Wila Yustini; Abdul Hamid Usman; Syalwa Rizki Syaqila; Nurul Safitri (Unram Journal of Community Service, 2026)
This community service program aims to enhance the understanding of the residents of Seri Dalam Village, Tanjung Raja Subdistrict, Ogan Ilir Regency, regarding land rights, land registration procedures (PTSL), land dispute mediation techniques, and the criminal aspects of land grabbing. The program was carried out through educational and consultative legal counseling, involving 25 participants, mostly landowners of plantations. Evaluation results show a significant improvement in the participants' knowledge, with high N-Gain scores (above 0.7) across all assessed indicators. The greatest improvement was seen in the understanding of the urgency of land certificates as a valid legal proof of ownership (53%). Additionally, the program successfully educated participants on land dispute mediation procedures and reinforced the role of the Village Head as the Village Peace Judge. As a sustainable output, a land legalization procedure module was handed over to the village office to be used as a guide in managing land administration services. This program is expected to raise legal awareness and improve land administration order in the village, as well as contribute to the economic stability of the community through more orderly and legal land management. Moving forward, similar programs should be expanded to have a greater impact on empowering communities based on agrarian law.